A revision of the "Belciana" viridipicta (Hampson, 1902) species group with description of a new genus and two new species from East Asia (Lepidoptera, Noctuidae: Pantheinae). Revision of Pantheinae, Contribution VII - Behounek, G.; Kononenko, V. S. (Zootaxa, 2012)
The new genus Viridistria gen. n. (type-species Ancara viridipicta Hampson, 1902) is separated and described from the heterogeneous complex “Belciana.” Two new species, Viridistria secreta sp. n. and Viridistria hollowayi sp. n. are described from North Vietnam, Sumatra and Borneo. Three new combinations are introduced: Viridistria thoracica (Moore, 1882) comb. n., Viridistria viridipicta (Hampson, 1902), comb. n. and Viridistria striatovirens (Moore, 1883), comb. n.). The adults, male and female genitalia are illustrated. A checklist of the genus Viridistria is presented.